GUI based Testing Tool for Transformer - K. Suryasen; K.V. Devadas; Harish. A (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The objective of this paper is to develop an educational toolbox using GUI for analysis of transformers for students and lecturers.  GUI figure file is developed for Open Circuit & Short Circuit Test, Sumpner’s Test, All day efficiency (Energy efficiency) of transformer and parallel operation of two transformers.  All this kinds of problems consists of various methods of mathematical calculation which is difficult to perform by using manual calculation (formula and calculator). The existence of this educational toolbox will help the user to calculate the parameter hence the calculation become faster and easier. The user can enter the data and obtained the results quickly in the form of data or figures.  The students can also observe the effect of variation of input parameters on performance of transformer.   This educational toolbox was developed by using MATLAB software.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5213